Analysis Of Behavior Change Communication In Counseling By The National Narcotics Agency Of South Kalimantan Province In Preventing Narcotics Abuse Among The Younger Generation (A Study From An Islamic Communication Perspective) - Amelia Puspita; Nasrudin Nasrudin; Decky Kuncoro; Devia Hetty Hernany (SAHAFA: Journal of Islamic Communication, 2026)
Drug abuse remains a major public health and social issue, particularly among young people who are highly vulnerable due to peer influence, curiosity, and environmental factors. As the leading institution responsible for drug prevention in Indonesia, the National Narcotics Agency (BNN) of South Kalimantan Province implements educational outreach programs to encourage behavioral change. This study aims to analyze the implementation of Behavior Change Communication (BCC) in BNN South Kalimantan Province's anti-drug awareness campaigns for young people from the perspective of Islamic communication. A qualitative case study approach was employed. Data were collected through observations, in-depth interviews with BNN officials, counselors, and outreach participants, as well as documentation. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while source and technique triangulation were applied to ensure data credibility. The findings reveal that the implementation of BCC incorporates four main components: communication messages, communication media, communication methods, and target audiences. Communication messages are developed based on current national drug abuse data, while visual and audiovisual media enhance participants' understanding. Interactive methods, including lectures, discussions, question-and-answer sessions, quizzes, and ice-breaking activities, encourage active participation. Furthermore, communication strategies are tailored to audience characteristics, particularly students and university students who are considered high-risk groups. From the perspective of Islamic communication, the implementation reflects the principles of bil hikmah, mau'izhah hasanah, and the protection of life (hifz al-nafs) and intellect (hifz al-'aql). The study concludes that integrating BCC with Islamic communication principles strengthens the effectiveness of anti-drug prevention campaigns by fostering awareness, positive attitudes, and sustainable behavioral change among young people. Keywords: Behavior Change Communication; Drug Abuse Prevention; National Narcotics Agency; Youth; Islamic Communication.